Religião e solidariedade : Dom Helder Camara e a cáritas brasileira - Costa, José Hamilton da (2011)
The practice of solidarity and social inclusion promoted by Dom Helder Camara, through the institutions and activities that created and / or supported, resulted from the principles relating to human development adopted by him in his pastoral career as a Brazilian religious leadership. In this work, we highlight the period from 1952 to 1964 and it was focused on reconstruction and analysis of the foundation and first years of Caritas Brasileira. The approach on the relationship between religion and solidarity is characterized in this thesis, as actual reality, the initiatives coming from a Church representative who offered to serve the poorest. So he created and / or supported structures plausible cooperation between people, communities and the state. The analysis of accumulated experience in building initiatives of various institutions, for example, the CNBB, Crusade San Sebastian and the Bank of Providence, made possible, in dialogue with primary sources cited and the theoretical work, say that the strategy social interaction, caused countless times by Dom Helder, contributed to the promotion of Christian practice and the lives of people in that period were involved in the walks of society and the Catholic Church. The object of this analysis has focused on building the institutions that approached the Church of the faithful and their care activities